Penyelesaian Utang Debitur dalam Keadaan Insolven: Perspektif Hukum Positif dan Hukum Islam - Wahyuni, Wenni; Cahyani, Andi Intan; Suriyadi, Suriyadi; Anggara, Bayu (Universitas Islam Negeri Alauddin Makassar, 2024)
This study discusses the settlement of debts of debtors who are insolvent from the perspective of positive law and Islamic law, in providing answers related to how to postpone debt payment obligations to insolvent debtors. This research is a library research with a juridical-normative approach. The sources of data used in this research are laws, the Qur'an and Sunnah, in addition to the method of data collection and data analysis by collecting various literature both books and journals then observing and analyzing the data which is the object of research and then providing conclusions. In this study it was found that the postponement of debt payment obligations to insolvent debtors according to Law no. 37 of 2004 concerning Bankruptcy and Suspension of Obligations for Debt Payment is an alternative that can be taken by insolvent debtors who are certain to be unable to pay their debts so that the company is not bankrupted by the court on the condition that during the PKPU period the debtor must submit a peace plan in the form of an offer to pay the debt as a whole or some of its debts or can even restructure its debts to its creditors. Meanwhile, the perspective of Islamic law regarding the postponement of debt payment obligations to insolvent debtors is that this is mubah contained in the Word of Allah swt QS. al-Baqarah/2:280. in the verse it is said that if someone owes him in trouble then give a grace period until he gets relief.